Risk Factors for Recurrence of Intracranial Aneurysm After Coil Embolization: A Meta-Analysis - Jin, Ji; Guo, Geng; Ren, Yeqing; Yang, Biao; Wu, Yongqiang; Wang, Shule; Sun, Yanqi; Wang, Xiaogang; Wang, Yuxiao; Zheng, Jianzhong (Frontiers in Neurology, 2022)
Intracranial aneurysm is a severe cerebral disorder involving complicated risk factors and endovascular coiling is a common therapeutic selection for intracranial aneurysm. The recurrence is a clinical challenge in intracranial aneurysms after coil embolization. With this study, we provided a meta-analysis of the risk factors for recurrence of intracranial aneurysm after coil embolization. Nine studies were included with a total of 1270 studies were retrieved from the database. The sample size of patients with intracranial aneurysms ranged from 241 to 3530, and a totally 9532 patients were included in the present meta-analysis. The intracranial aneurysms that occurred in middle cerebral artery (MCA) (OR=1.09, 95% CI:1.03-1.16, P=0.0045) and posterior circulation (OR=2.01, 95% CI:1.55-2.60, P=0.000) presented the significantly higher risk of recurrence after coil embolization. Meanwhile, intracranial aneurysms of size > 7 mm (OR=5.38, 95%CI:3.76-7.70, P=0.000) had a significantly higher risk of recurrence after coil embolization. Moreover, ruptured aneurysm (OR=2.86, 95% CI:2.02-4.04, P=0.000) and subarachnoid hemorrhage (SAH) (OR=1.57, 95% CI:1.20-2.06, P=0.001) was positively correlated with the risk of recurrence after coil embolization. In conclusion, this meta-analysis identified the characteristics of intracranial aneurysms with MCA, posterior circulation, size > 7 mm, ruptured aneurysm, and SAH as the risk factors of recurrence after coil embolization for intracranial aneurysms.